2023
DOI: 10.1111/jors.12641
|View full text |Cite
|
Sign up to set email alerts
|

The spatial scope of agglomeration economies in Brazil

Abstract: This paper provides evidence about location and colocation patterns of manufacturing entrepreneurship and spatial scope of agglomeration economies in the context of a developing country. Using microgeographic data for all Brazilian manufacturing activities and distance‐based measures, we find clear patterns of colocalization between entrants and existing establishments, and that these patterns occur mainly at short distances. For activities presenting colocalization between entrants and existing establishments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Thereby, the distance-based method based on the DO index has become the predominant method for measuring industrial agglomeration degrees of regions [17]. It has been widely used in studies of industrial agglomeration in the country, urban agglomeration, and inner city levels [19,20,23,39,[43][44][45][46][47][48][49][50][51]. Nevertheless, the DO index method still faces challenges, such as a lack of explanations on the result curves, low accessibility of micro-data on firms, and ignorance of cluster locations [21,22,52].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the distance-based method based on the DO index has become the predominant method for measuring industrial agglomeration degrees of regions [17]. It has been widely used in studies of industrial agglomeration in the country, urban agglomeration, and inner city levels [19,20,23,39,[43][44][45][46][47][48][49][50][51]. Nevertheless, the DO index method still faces challenges, such as a lack of explanations on the result curves, low accessibility of micro-data on firms, and ignorance of cluster locations [21,22,52].…”
Section: Introductionmentioning
confidence: 99%
“…produced structural estimates of the strength of agglomeration economies within Berlin based on the changes induced by the construction and fall of the Berlin Wall and concluded that strong productivity effects of proximity exist that dissipate very rapidly, reaching zero at ten minutes of travel time. In Latin America, a recent study byAlmeida, Neto, and Rocha (2023) showed strong effects in Brazil of own-industry employment on firm creation and new-firm employment within one kilometer that dissipated with distance and disappeared after five kilometers.Distance to the most agglomerated areas of the city may also play a role in the persistence of labor informality. Informal workers can draw major advantages from agglomeration-in fact, studies in Latin America have frequently found larger productivity effects of agglomeration in the informal than the formal sector(Duranton 2016;Bernedo Del Carpio and Patrick 2021; Quintero and Roberts 2022;.4 While the drivers for this difference are still understudied, it is likely related to access to customers.…”
mentioning
confidence: 99%